Morphology and Climatology of Nighttime Periodic Ionospheric TEC Disturbances Associated With MSTIDs Over China - Ke Li; Donghe Zhang; Yi Zeng; Yaoyu Tian; Guanglin Yang; Yongqiang Hao (Space Weather)
Abstract In this study, the morphology and climatology of the nighttime periodic disturbances associated with medium‐scale traveling ionospheric disturbances (MSTIDs) are investigated over the entire China sector from January 2014 to August 2017, using data from global navigation satellite systems (GNSS) receivers. Firstly, a comparative case analysis of propagation characteristics reveals the complexity and day‐to‐day variations of nighttime MSTID activity. The main statistical findings indicate that these periodic disturbances predominantly occur during the summer months, with a higher occurrence rate during solar minimum. In summer, the disturbances occur more frequently in regions with lower latitudes (20–35°N) and tend to exhibit an extended duration. In the meantime, some disturbances are also detected at much lower latitudes (<20°N), with noticeable longitudinal differences. Additionally, there are two peaks in the geographic distribution of disturbances, located in the sector of 90–100°E and 105–125°E at lower latitudes, respectively. The distinct spatiotemporal evolution patterns of the two peak disturbance regions suggest that their formation mechanisms should be different. The disturbances in the eastern region exhibit similarities with electrified MSTIDs, which are closely related to Perkins instability, whereas the western disturbance region does not display apparent movement, but exhibits a higher occurrence rate and longer durations, which may be attributed to the frequent upward propagation of GWs in the southeastern region of the Qinghai‐Tibet Plateau.